2021
DOI: 10.1093/trstmh/trab107
|View full text |Cite
|
Sign up to set email alerts
|

Real-time polymerase chain reaction on filter paper spotted samples: a gateway to molecular diagnosis of invasive bacterial diseases for rural areas in low-income countries

Abstract: Background Bacterial culture is the gold standard for the diagnosis of invasive bacterial diseases (IBDs) but molecular methods are more specific and sensitive. Fresh liquid samples (FLSs) show patent limitations for shipping and storage. We aimed to evaluate the sensitivity and specificity of real-time polymerase chain reaction (PCR) performed on dried sample spots (DSSs) obtained from different biological fluids compared with real-time PCR or culture performed on FLSs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Our dried blood spot assay using the crude DNA extraction method showed a high sensitivity (89%) and specificity (99%) for the detection of Nm in dried blood spots. These results are comparable to the sensitivity and specificity of 90.3% and 99%, respectively reported by De Vitis and colleagues for their dried spot assay which utilised the MagCore automated NucleicAcid Extractor with MagCore Nucleic Acid Tissue Extraction Kit [ 22 ]. Crude DNA extraction from blood and other clinical specimens therefore could be a viable alternative to traditional extraction kits and make dried spot assays for the diagnosis of bacterial meningitis more accessible in resource-limited settings.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our dried blood spot assay using the crude DNA extraction method showed a high sensitivity (89%) and specificity (99%) for the detection of Nm in dried blood spots. These results are comparable to the sensitivity and specificity of 90.3% and 99%, respectively reported by De Vitis and colleagues for their dried spot assay which utilised the MagCore automated NucleicAcid Extractor with MagCore Nucleic Acid Tissue Extraction Kit [ 22 ]. Crude DNA extraction from blood and other clinical specimens therefore could be a viable alternative to traditional extraction kits and make dried spot assays for the diagnosis of bacterial meningitis more accessible in resource-limited settings.…”
Section: Discussionsupporting
confidence: 79%
“…Of the 213 dried CSF specimens, they tested for Nm, S. pneumoniae and Haemophilus influenzae , the specificities were 100% and the sensitivities ranged from 96 to 100% across all three pathogens. Likewise, De Vitis and colleagues found that among 44 CSF specimens for which a bacterial infection was confirmed by qPCR of the liquid specimen, 41 (93.2%) were positive by testing on dried filter paper [ 22 ]. Our study provides further evidence that compared to real-time PCR on liquid specimens, dried filter spot assays are highly specific and sensitive for the detection of Nm in CSF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation